2017
DOI: 10.1002/pro.3275
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenesis of Tau protein

Abstract: The role of microtubule-associated protein Tau in neurodegeneration has been extensively investigated since the discovery of Tau amyloid aggregates in the brains of patients with Alzheimer's disease (AD). The process of formation of amyloid fibrils is known as amyloidogenesis and attracts much attention as a potential target in the prevention and treatment of neurodegenerative conditions linked to protein aggregation. Cerebral deposition of amyloid aggregates of Tau is observed not only in AD but also in numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
127
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 299 publications
(631 reference statements)
1
127
0
6
Order By: Relevance
“…Especially the 42-amino acid fragment (Aβ ) easily aggregates and self-assembles to form a heterogeneous mixture of oligomers and protofibrils, which ultimately deposit in senile plaques. Small soluble Aβ oligomers are considered as the major neurotoxic species in AD (9). Aβs have been reported to induce apoptosis in neuronal cells by mitochondrial dysfunction and oxidative 2 , and incubated to achieve complete cell attachment.…”
Section: Ammonium Hydroxide Results: Se Showed Hormetic Growth Stimumentioning
confidence: 99%
“…Especially the 42-amino acid fragment (Aβ ) easily aggregates and self-assembles to form a heterogeneous mixture of oligomers and protofibrils, which ultimately deposit in senile plaques. Small soluble Aβ oligomers are considered as the major neurotoxic species in AD (9). Aβs have been reported to induce apoptosis in neuronal cells by mitochondrial dysfunction and oxidative 2 , and incubated to achieve complete cell attachment.…”
Section: Ammonium Hydroxide Results: Se Showed Hormetic Growth Stimumentioning
confidence: 99%
“…After analyzing the effect of NR on the physiopathology and cellular mechanisms in the 3xTgAD/Polß ± mouse model (mice deficient in DNA repair that exacerbates the main characteristics of AD in humans) it was observed that supplementation with NR significantly increased the NAD + /NADH ratio, reduced neuroinflammation, apoptosis and damage to DNA, increased neurogenesis, restored synaptic plasticity, improved learning capacity and reversed memory deficits (Hou et al, 2017a). Treatment with NR improves cognition in transgenic mice with AD by reducing the phosphorylation of the Tau protein (pTau) (a form that accumulates in the brain of AD patients and is the hallmark of the disease) (Green et al, 2008;Rüb et al, 2017;Nizynski et al, 2017). In the case of PD, the repletion of NAD + through the use of NR prevents aging related to the loss of dopaminergic neurons and the reduction of motor function in Drosophila fly model of PD (Sidransky et al, 2009).…”
Section: Nicotinamide Ribosidementioning
confidence: 99%
“…Several proteins self-associate into amyloid fibrils, which in some cases have functional roles [1][2][3] , but for others are associated with debilitating human diseases [4][5][6] including Alzheimer's Disease, Parkinson's Disease, Huntington's Disease, type II diabetes, cataracts, and Dialysis Related Amyloidosis (DRA). The protein precursors of amyloid diseases have unrelated primary sequences and structures 7 , spanning natively unfolded (intrinsically disordered) states, such as α-synuclein, amyloid-β peptide, and tau [8][9][10] , to stable, globular proteins, such as β 2microglobulin (β 2 m), transthyretin, and immunoglobulin light chains [11][12][13] . Initiation of amyloid formation of the latter class of proteins requires unfolding or partial unfolding of monomeric precursors, which can transiently assume amyloid-competent state(s).…”
Section: Introductionmentioning
confidence: 99%